Investigating the potential impacts and interactive effects of climate warming and multi-gear fishing on the Eastern Ionian Sea ecosystem using EwE and ecological indicators - Papantoniou, Georgia; Sgardeli, Vasiliki; Vassilopoulou, Vassiliki; Tsagarakis, Konstantinos (Frontiers in Marine Science, 2025)
IntroductionCurrent manifestations of anthropogenic stressors on coastal ecosystems have intensified the need for a more profound understanding of trophic interactions, particularly under the ongoing climate change that is triggering the rewiring of food webs globally.MethodsHerein, we present the development of an Ecopath model for the Eastern Ionian Sea (EIS; Central Mediterranean) in 1998-2000, the parameterization and fitting of the dynamic module Ecosim to biomass and catch data from 2000 to 2020, and future projections of the ecosystems’ responses to a set of single and multiple stressor scenarios for the period 2021-2080. The 21 simulations consisted of two levels of climate change and total and gear-specific fishing effort reduction. We estimated the cumulative impact of multiple stressors on ecosystem dynamics, with emphasis on stressor interactions (synergistic vs. antagonistic) and addressed the response of ecological indicators estimated in broad functional groups (e.g. trophic guilds, pelagic and demersal resources), to identify those that best track perturbation-induced shifts.ResultsThe EIS is a moderately complex oligotrophic ecosystem, where exploitation indices classified fishing activities as sustainable, yet some stocks remain overexploited (e.g., hake, cuttlefish). The integration of trophic interactions, climate warming, fishing activity, and primary production enhanced the model's accuracy, indicating that both anthropogenic exploitation and environmental factors have historically shaped ecosystem dynamics. Future simulations highlighted that the high-baseline carbon emission scenario (RCP8.5) intensified ecosystem changes, compared to the scenario of moderate carbon mitigation (RCP4.5) after 2050. Moreover, antagonistic stressor interactions that persisted throughout the projection period under combined RCP4.5 scenarios shifted to synergistic by the latter half of the century (2080) under RCP8.5, resulting in negative effects on the biomass of most functional groups and raising serious concerns for future stock sustainability, as synergistic effects of stressors may non-linearly increase adverse impacts on ecosystems. Indicators showed that multiple stressors led to less abundant, less diverse, and lower trophic level benthivore communities, while piscivores were particularly vulnerable to warming, supporting projections of top-predator declines.DiscussionOur findings emphasize the urgency of utilizing the window of opportunity until 2050 to integrate climate-adaptive measures into fisheries management in order to prevent future declines of Mediterranean marine resources.